2019
DOI: 10.3390/met9020163
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure to Fine Particles and Ultrafine Particles in a Steelmaking Foundry

Abstract: Several studies have shown an increased mortality rate for different types of tumors, respiratory disease and cardiovascular morbidity associated with foundry work. Airborne particles were investigated in a steelmaking foundry using an electric low-pressure impactor (ELPI+™), a Philips Aerasense Nanotracer and traditional sampling equipment. Determination of metallic elements in the collected particles was carried out by inductively coupled plasma mass spectrometry. The median of ultrafine particle (UFP) conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Many studies have shown that UFPs can contribute to adverse health effects in life and work environments [5][6][7][8][9][10][11], measurable also over time in terms of health burden of related diseases [12]. UFPs are very small compared with the cellular structures and so this may be important in the consequences they may cause to the lung [13].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that UFPs can contribute to adverse health effects in life and work environments [5][6][7][8][9][10][11], measurable also over time in terms of health burden of related diseases [12]. UFPs are very small compared with the cellular structures and so this may be important in the consequences they may cause to the lung [13].…”
Section: Introductionmentioning
confidence: 99%
“…UFPs concentration in the atmosphere can have a strong spatial and temporal variations and personal sampling can be more accurate than stationary sampling to assess UFPs personal exposure [13]. Recently, some studies have focused on UFPs personal exposure assessment in living and working environments [14][15][16]. However, to date there are still few studies about UFPs personal exposure in the living and working environment [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…This Special Issue published 33 high quality articles from 10 countries (according to the country of the corresponding author) with the number of contributions in brackets: China (22) , Japan (1) [23], Korea (1) [24], Canada (1) [25], Sweden (2) [26,27], Italy (1) [28], UK (1) [29], France (1) [30], Austria (1) [31], and Slovakia (2) [32,33]. This clearly reflects the enormous investment in R&D in China and the resultant outstanding outcomes to support its steel industry with~50% of global steel production.…”
Section: Contributionsmentioning
confidence: 99%
“…An interesting contribution from Italy (Marcias et al [28]) thoroughly analysed the occupational exposure to fine particles and ultrafine particles in a steelmaking foundry. This is a critical aspect of steel industry considering the environment of the steel manufacturing lines.…”
Section: Contributionsmentioning
confidence: 99%